The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/pssc.201001126
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for moving of threading dislocations during the VPE growth in GaN thin layers

Abstract: Cross‐sectional transmission electron microscope (TEM) observation was performed in detail to analyze the morphology of threading dislocations (TDs) in GaN thin layers with various thicknesses. The GaN layers were overgrown on an Al0.28Ga0.72N layer by the metal‐organic vapor‐phase epitaxy (MOVPE) method. In a GaN layer about 50 nm in thickness, TDs running up in the AlGaN layer pass into the GaN layer and most of them reach the top surface without bending. In thicker GaN layers, on the other hand, many of TDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…7) The formation of hairpins due to stress relief through the interaction between inclined TDs was also reported. 8) A similar inclination of a-type TDs for strain relaxation was also found in undoped AlGaN layers grown on AlN. [9][10][11][12] Notably, most of the previous works focused on the strain relaxation by TD inclination in an AlGaN single layer as well as the effect of Si dopants on the TD inclination, but few experimental results on AlGaN-related multilayered materials with Mg dopants were reported.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…7) The formation of hairpins due to stress relief through the interaction between inclined TDs was also reported. 8) A similar inclination of a-type TDs for strain relaxation was also found in undoped AlGaN layers grown on AlN. [9][10][11][12] Notably, most of the previous works focused on the strain relaxation by TD inclination in an AlGaN single layer as well as the effect of Si dopants on the TD inclination, but few experimental results on AlGaN-related multilayered materials with Mg dopants were reported.…”
mentioning
confidence: 54%
“…3, are also formed in the vicinity of the GaN/AlGaN-SL/AlN interface, which was generally considered to result from the interaction between inclined TDs. 8) The inclination of a þ c-type dislocations indicated that the effect of HT-AlN IL is different with the lowtemperature AlN IL, which has no effect on the bending of a þ c-type TDs. 16) To clarify the relaxation mechanism, we also did the planview TEM measurements.…”
mentioning
confidence: 97%
“…In our opinion [2] the possible origin of this stress is the climb of threading dislocations [3]. The transport of point defects, responsible for the dislocation climb, may occur in bulk [4,5] or at the surface [6,7].…”
Section: Introductionmentioning
confidence: 95%
“…4) Such In segregation in InGaN quantum well causes discontinuity of quantum well stack and intermixing in the vicinity of the dislocations. 5) The low-temperature buffer layer technique and epitaxial lateral overgrowth (ELO) [6][7][8][9] have been proposed to reduce TDs in the GaN/Al 2 O 3 heteroepitaxial growth system. On the basis of the results of cross-sectional transmission electron microscopy (TEM), Sakai et al reported that the TDs transmitted from the substrates were drastically reduced in the GaN films grown selectively in HVPE.…”
Section: Introductionmentioning
confidence: 99%